I want to change I don't know how ([USA] : Cally Curtis, 1988)
This is a film about making positive changes in your life. The film offers specific'how to' steps to take before, during and after your change to make it a reality
Backup available in VHS
Bibliographical information is taken from the publisher's catalogue
Copy available in VCD format
Keywords: Change (Psychology); Motivation; Personality change